THU0149 Comparison of ACR/EULAR and DAS28 Remission Criteria in a Cohort of TNF Inhibitor Treated Rheumatoid Arthritis Patients. (23rd January 2014) - Balogh, E.; Dias, J. M.; Mullan, R.; Harty, L. C.; Gallagher, P.; Molloy, M.; O'Flynn, E.; O'Kelly, A.; O'Neill, M.; Moore, L.; Murray, M.; FitzGerald, O.; et al.
Abstract : Background: Early diagnosis and remission-oriented treatment are essential to achieve good outcomes in rheumatoid arthritis (RA). New RA remission criteria have been developed by American College of Rheumatology/The European League Against Rheumatism (ACR/EULAR) in 2011. Objectives: Remission rates of tumor necrosis factor inhibitor (TNFi) treated RA patients were compared using ACR/EULAR and DAS28-4 variable-CRP (DAS28(4v)-CRP) remission criteria. Methods: Clinical and laboratory data were collected prospectively of 273 biologic naive RA patients commencing TNFi therapy at 0, 3, 6, 12 months. Remission status was calculated at all timepoints using ACR/EULAR Boolean and DAS28(4v)-CRP <2.6 remission criteria. Response was scored using EULAR response criteria. Statistics were made using SPSS v20. Results: Mean (range) patient age was 59.9 (7.2-85.4) years with disease duration of 13.4 (1.0-52.0) years. In total 86% of patients were responders (37% good; 50% moderate) at 3 months and maintained, with a further increase, at 12 months (51% good; 32% moderate). Laboratory and clinical parameters (erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), patient global health (PGH), DAS28(4v)-CRP showed significant sustained improvement at 3 and 12 months of therapy (p<0.05). Over half of patients (54.9%) had disease activity of DAS28(4v)-CRP<3.2 at 12 months. All patients in Boolean remission were in DAS28 remission at all timepoints. 102 patients (37%) were in any remission at 12 months: 75 (27%) in DAS28 remission alone and 27 (10%) in both Boolean and DAS28 remission. We further compared remsission statuses at one year. All patients in any remission were significantly younger (p=0.041) with lower baseline tender joint count 28 (TJC28) and patient global health (PGH) scores than those not in remission (p=0.001, p=0.047). Boolean-remission patients were younger (p=0.026) and had lower 12 months DAS28 and PGH (all p<0.0001). Disease activity of the most active Boolean remission patient was found to be 1.97 calculated by DAS28(4v)-CRP. Patients not achieving Boolean remission due to missing just one Boolean subcriteria being ≤1 (30.77 %), most frequently missed PGH ≤1 criteria (76.2 %). Conclusions: Only 10% of this TNFi treated RA cohort achieved remission according to the new ACR/EULAR criteria, which originally requires lower disease activity state for remission. Failing Boolean remission due to the lack of one subcriteria was often resulted by primarily higher PGH values. This may reflect a delay in initiating biologic therapy and support earlier, more aggressive therapy in RA. References: Rheumatoid arthritis disease activity measures: American College of Rheumatology recommendations for use in clinical practice. Anderson J et al. Arthritis Care Res (Hoboken). 2012 May;64(5):640-7. American College of Rheumatology/European League Against Rheumatism provisional definition of remission in rheumatoid arthritis for clinical trials. Felson DTet al.; American College of Rheumatology; European League Against Rheumatism. Arthritis Rheum. 2011 Mar;63(3):573-86. Acknowledgements: Translational Research Group, DAMC, SVUH Disclosure of Interest: E. Balogh Grant/research support from: MSD, J. Dias: None Declared, R. Mullan: None Declared, L. Harty: None Declared, P. Gallagher: None Declared, M. Molloy: None Declared, E. O'Flynn: None Declared, A. O'Kelly: None Declared, M. O'Neill: None Declared, L. Moore: None Declared, M. Murray: None Declared, O. FitzGerald: None Declared, U. Fearon: None Declared, D. Veale Grant/research support from: Abbott, Opsona, Pfizer, Roche, Consultant for: MSD, Pfizer, Roche, Speakers bureau: Janssen, MSD, Pfizer, UCB